2008
DOI: 10.1158/1078-0432.ccr-07-4129
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Array-Based Comparative Genomic Hybridization of Bladder Cancers IdentifiesMouse Double Minute 4(MDM4) as an Amplification Target Exclusive ofMDM2andTP53

Abstract: Purpose: Loss of p53 function in urothelial cell carcinoma (UCC) by mutation or inactivation disrupts normal cell cycle checkpoints, generating a favorable milieu for genomic instability, a hallmark of UCC. The aim of this study was to characterize novel DNA copy number changes to identify putative therapeutic targets. Experimental Design:We report our findings using array comparative genomic hybridization on a whole-genome BAC/PAC/cosmid array with a median clone interval of 0.97 Mb to study a series of UCC c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 41 publications
3
29
0
Order By: Relevance
“…Interestingly, the 1q locus containing the gene encoding MDM4, a known inhibitor of p53 was repeatedly found to be amplified in post-MPN AML [45,59]. As previously reported in solid tumors [131], gains of 1q were mutually exclusive with p53 mutations, indicating that these two genetic lesions affect the same pathway, which then seems to contribute to 45.5 % of the post-MPN AML cases [130]. The significance of this pathway in leukemic transformation is further supported by the finding that TP53 mutations are the only independent prognostic factor of poor survival in secondary AML [59].…”
Section: Genetic Aberrations Associated With Disease Progressionsupporting
confidence: 63%
“…Interestingly, the 1q locus containing the gene encoding MDM4, a known inhibitor of p53 was repeatedly found to be amplified in post-MPN AML [45,59]. As previously reported in solid tumors [131], gains of 1q were mutually exclusive with p53 mutations, indicating that these two genetic lesions affect the same pathway, which then seems to contribute to 45.5 % of the post-MPN AML cases [130]. The significance of this pathway in leukemic transformation is further supported by the finding that TP53 mutations are the only independent prognostic factor of poor survival in secondary AML [59].…”
Section: Genetic Aberrations Associated With Disease Progressionsupporting
confidence: 63%
“…4) and the other at 1q32, harbouring among others the MDM4 gene. These genes deserve attention as expression of CTSK has been linked with invasiveness in breast cancer (Kleer et al 2008), and the MDM4 locus has recently been found to be amplified in bladder cancer, with associated overexpression of MDM4 and disruption of TP53 activity (Veerakumarasivam et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…49 In this context, 1q gains (ie, MDM4 amplifications) are mutually exclusive with TP53 mutations, a phenomenon also observed in solid tumors. 50 Overexpression of MDM4 has also been reported in CLL, which responds poorly to the MDM2 inhibitor Nutlin, implicating MDM4 as an important p53 inhibitor in CLL. 51 Altogether, these data highlight the importance of dampening p53 levels in transformation of the hematopoietic system.…”
Section: P53 Deregulation In Hematopoietic Tumorsmentioning
confidence: 99%